2016
DOI: 10.1002/adma.201505281
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Pt as Co‐Catalyst for Enhanced Photocatalytic H2 Evolution

Abstract: Isolated single-atom platinum (Pt) embedded in the sub-nanoporosity of 2D g-C3 N4 as a new form of co-catalyst is reported. The highly stable single-atom co-catalyst maximizes the atom efficiency and alters the surface trap states of g-C3 N4 , leading to significantly enhanced photocatalytic H2 evolution activity, 8.6 times higher than that of Pt nanoparticles and up to 50 times that for bare g-C3 N4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
806
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,265 publications
(847 citation statements)
references
References 34 publications
21
806
1
2
Order By: Relevance
“…In the case of carbon nitride, the selective breaking of abundant hydrogen bonds in the intralayer framework not only extends visible light absorption range but also suppresses the radiative electron-hole recombination as demonstrated by Figure 4 , whose origin is the increased low-energy photon excitations and band-to-tail charge transfer processes induced by the increased band tails/localized states close to the band edges. In contrast, for the carbon nitride with broken hydrogen bonds the deposited Au particles with a relatively uniform particle size of around 10 nm (a small particle size of noble metal as co-catalyst favors the transfer of photoexcited electrons from a semiconductor to co-catalyst [ 35 ] ) are well dispersed through the whole carbon nitride particles. In addition to these electronic structure-induced favorable features, the abundant interconnected pores through the whole particles simultaneously formed by breaking hydrogen bonds play an important role in geometrically shortening the diffusion lengths of both the photoexcited electrons from the interior to edges of the layers and reactants from the surface to the interior of a particle along the interlayer galleries.…”
Section: Communicationmentioning
confidence: 64%
“…In the case of carbon nitride, the selective breaking of abundant hydrogen bonds in the intralayer framework not only extends visible light absorption range but also suppresses the radiative electron-hole recombination as demonstrated by Figure 4 , whose origin is the increased low-energy photon excitations and band-to-tail charge transfer processes induced by the increased band tails/localized states close to the band edges. In contrast, for the carbon nitride with broken hydrogen bonds the deposited Au particles with a relatively uniform particle size of around 10 nm (a small particle size of noble metal as co-catalyst favors the transfer of photoexcited electrons from a semiconductor to co-catalyst [ 35 ] ) are well dispersed through the whole carbon nitride particles. In addition to these electronic structure-induced favorable features, the abundant interconnected pores through the whole particles simultaneously formed by breaking hydrogen bonds play an important role in geometrically shortening the diffusion lengths of both the photoexcited electrons from the interior to edges of the layers and reactants from the surface to the interior of a particle along the interlayer galleries.…”
Section: Communicationmentioning
confidence: 64%
“…Li et al [202] reported singleatom Pt as cocatalyst for enhanced photocatalytic H 2 evolution of gC 3 (Figure 17a) demonstrated that the Pt atoms are uniformly dispersed on the surface of gC 3 N 4 , and the sizes of 99.4% of Pt species are below 0.2 nm. As is well known, the heterogeneous catalytic reactions are surface reactions.…”
Section: G-c 3 N 4 /Metal Heterostructurementioning
confidence: 99%
“…[6,7] Atomically dispersed catalysts comprising mononuclear metal complexes or single metal atoms provide as uitable model for atomic-level insight into reaction kinetics of the active site. [12] Recently,t he synthetic cobalt-based complexes containing square planar-like "Co 1 -N 4 "single active site have been explored as effective H 2 -evolution catalysts. [12] Recently,t he synthetic cobalt-based complexes containing square planar-like "Co 1 -N 4 "single active site have been explored as effective H 2 -evolution catalysts.…”
mentioning
confidence: 99%
“…[20] Theunsaturated Nwith an electron lone pair is an ideal anchoring site for immobilizing metal ions into C 3 N 4 framework. [12] Co ALD was performed using bis(cyclo-pentadienyl)cobalt, Co(Cp) 2 ,followed by O 3 treatment under as hort time of 150 sa nd ar elatively low temperature of 150 8 8Ct or emove the surface Cp ligand. It should be noted that the phosphidation and Co ALD process would not largely influence the morphology and main matrix network of g-C 3 N 4 (Supporting Information, Figures S1, S2).…”
mentioning
confidence: 99%